GAMBARAN STRES DAN STRATEGI KOPING IBU HAMIL SELAMA PANDEMI COVID-19 DI WILAYAH PUSKESMAS II DENPASAR BARAT - Wulandari, Ida Ayu Made Widnyani; Astuti, Ika Widi; Yanti, Ni Luh Putu Eva (Coping: Community of Publishing in Nursing; Vol 10 No 1 (2022): Februari 2022DO - 10.24843/coping.2022.v10.i01.p10, 2022)
Stress during pregnancy is a mother’s emotional reaction during pregnancy due to physical and psychological changes. The COVID-19 pandemic can be a source of stress for pregnant women. They will show coping behavior towards stress as a response to the stress they are facing. This study aims to determine the description of stress and coping strategies used by pregnant women in undergoing the pregnancy process during the COVID-19 pandemic in the Work Area of ??Puskesmas II West Denpasar. This descriptive study implemented quantitative methods by using a cross-sectional research design. The sample amounted to 43 pregnant women selected using purposive sampling technique. The data were collected using a questionnaire (AIM) Affective Intensity Measure and cope scale. The results showed that the stress level of pregnant women in the process of pregnancy was in the mild category of 60.5%, the moderate category was 39.5% and there were no pregnant women who had severe stress. The results of the analysis of coping strategies for pregnant women are in the PFC (Problem Focused Coping) category of 76.7% and EFC (Emotion Focused Coping) category of 23.3%. The data from this study can be concluded that the stress level of pregnant women is in the low category and the chosen coping strategy is PFC (Problem Focused Coping). This research is expected to improve nursing practice, especially in the application of positive coping behaviors in dealing with stress in pregnant women.